Pengaruh Kualitas Layanan, Konflik Peran, dan Motivasi terhadap Kepuasan Masyarakat - Renil Septiano; Verafirma Verafirma; Lusiana Lusiana; Marwan Marwan; Indra Firmansyah (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study delves into the impact of public service excellence, the challenges of conflicting roles, and the drive for public service on community contentment in Pondok Tinggi, Sungai Penuh, highlighting both the direct and intermediary influences of these elements. Methodology: Employing a quantitative research methodology, this study gathered data from 144 respondents through surveys conducted between August and September 2024. The survey included various constructs related to public service, role conflict, and motivation, which were analyzed using statistical techniques provided by IBM SPSS software. Results: The findings revealed that the quality of public service significantly enhances community satisfaction, whereas role conflict negatively affects it. Moreover, public service motivation plays a crucial role in improving community satisfaction, suggesting a complex interplay between these variables. Conclusions: This study conclusively demonstrates that the quality of public service significantly enhances community satisfaction, whereas role conflict detracts from it. Furthermore, public service motivation significantly boosts this satisfaction, underscoring the critical interplay between these factors. By holistically examining these dynamics, this study provides valuable insights for local government policies aimed at improving public service delivery and community well-being in Pondok Tinggi, Sungai Penuh. Limitations: The main limitation of this study is its focus on a single locality, which may not fully represent other regions with different administrative dynamics. Contribution: This study enriches the body of knowledge surrounding public administration by illuminating the essential elements that influence community satisfaction and presenting tangible evidence derived from a local governmental setting in Indonesia.